Harnessing agro-waste for the high-efficiency removal of methylene blue using ball-milled magnetic Fe3O4@pistachio shell composites: From waste to resource - Tamer S. Saleh; Mohamed N. Gomaa; Abdullah Akhdhar; Abdullah S. Al‐Bogami; Waleed A. El-Said (PLoS ONE, 2025)
The development of a cost-effective and ecologically beneficial method for removing toxic dye molecules from wastewater is urgently needed for environmental and health reasons. Here, four Fe 3 O 4 /PS nanocomposites with different Fe 3 O 4 percentages were fabricated through the mechanochemical technique. This study provided a new monolithic adsorbent from abundant materials via a facile synthetic procedure, which can greatly reduce the problems of the tedious separation of adsorbents from treated waste. The adsorbent is composed of pistachio shell/Fe 3 O 4 composite, which has been used as a highly effective and sustainable adsorbent to eliminate methylene blue (MB) dye under ambient conditions. Diverse characterization analyses, including SEM, EDX, and FTIR techniques, were utilized to investigate the morphology and structure of the synthesized composite. The formed Fe 3 O 4 particles have an average diameter of 274 nm and an average area of 0.11 μm 2 . The batch adsorption methodology was employed, wherein several parameters, such as adsorbent dose, pH, initial dye concentration, adsorption temperature, and contact time, were adjusted to examine their effectiveness and adsorption capacity in removing the MB dye. Furthermore, the adsorption behavior was evaluated by studying the linear and non-linear adsorption isotherms. The maximum MB removal efficiency of 95% was achieved with the optimized parameters of MB dye concentration (2.5 mg/L), adsorbent dose (15 mg), contact time (15 min), and adsorption temperature (25 °C). The selectivity of the developed adsorbent was examined towards 25 mg/L of MB cationic dye and anionic dye (methylene orange), which demonstrated higher removal efficiency for the cationic dye (46.93%) compared to the anionic dye (12.46%). Moreover, the pistachio shell/Fe 3 O 4 adsorbent demonstrated excellent capability to remove MB dye from industrial wastewater samples. Overall, this approach presents a new, sustainable, and effective strategy for mitigating the harmful effects of MB, with potential applications in treated industrial wastewater samples.